A bimetallic MXene TiNbCT x / rGO / Fe3O4 composite aerogel, preparation method and application thereof

CN122875153APending Publication Date: 2026-10-09HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511989838.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-26
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,目前大多数研究都集中在Ti3C2TxMXene上,而忽视了对其他体系的MXene的研究

Benefits of technology

本发明采用四丁基氢氧化铵溶液对多层TiNbCTx进行插层处理,成功实现多层TiNbCTx的有效剥离,制备稳定的单层TiNbCTx分散液,解决了双金属MXene插层困难,单层分散液难以制备的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875153A_ABST
    Figure CN122875153A_ABST
Patent Text Reader

Abstract

The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a bimetallic MXene TiNbCT x The application discloses a b
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electromagnetic functional materials, specifically, it relates to a bimetallic MXene TiNbCT x / rGO / Fe3O4 composite aerogel, its preparation method and application, for microwave absorption. Background Technology

[0002] With the rapid development of technologies such as wireless communication, aerospace, and autonomous driving based on electromagnetic wave theory, people's lives have undergone tremendous changes. However, the increasingly serious electromagnetic pollution that follows also threatens people's health and information security. Therefore, how to prepare high-performance microwave absorbing materials has become a hot research topic.

[0003] In 2011, a novel class of two-dimensional layered transition metal carbides / nitrides, MXenes, was discovered. Benefiting from their excellent electrical conductivity, extremely high specific surface area, and diverse functional groups, MXenes have become a key research focus for addressing electromagnetic pollution problems. For example, Chinese patent CN121038259A prepared a Ti3C2T-based... x The multilayer structure of PANI opens stacked ion transport channels and modulates the conductivity of MXene material in situ, resulting in good electromagnetic shielding performance. Chinese patent CN120248528A prepared MXene / carbon fiber composite materials with good microwave absorption performance. However, most current research focuses on Ti3C2T... x The focus was on MXene, while neglecting research on MXene in other systems.

[0004] Furthermore, due to the single reflection loss and the impedance mismatch caused by excessively high complex permittivity and excessively low complex permeability, pure MXene cannot meet the requirements of thinness, wide bandwidth, and low reflection loss for modern electromagnetic wave absorbers. At the same time, the influence of microstructure on microwave absorption has not received sufficient attention.

[0005] In summary, how to prepare novel MXenes and introduce multiple loss mechanisms through customized microstructures and composite materials to achieve good electromagnetic wave absorption performance has become an urgent problem to be solved in the field of electromagnetic wave absorption for MXenes. Summary of the Invention

[0006] To avoid repetitive research on MXene materials and considering the influence of microstructure on microwave absorption performance, this invention provides a bimetallic MXene TiNbCT material to meet the requirements of modern electromagnetic wave absorbers. xThis invention relates to a method for preparing a TiNbCT / Fe3O4 composite aerogel. The method utilizes solid-state sintering, fluoride salt acid etching, hydrothermal reduction, and freeze-drying techniques to synthesize this aerogel. x The composite aerogel composed of Nb, rGO, and Fe3O4 exhibits multiple microwave loss mechanisms. The solid solution of Nb and the composite with Fe3O4 introduce strong polarization and magnetic losses, and effectively optimize impedance matching; the 3D porous aerogel structure facilitates multiple scattering of electromagnetic waves within the material. Thanks to the synergistic effect of conductivity loss, polarization loss, and magnetic loss, the composite aerogel possesses excellent microwave absorption performance.

[0007] To address the aforementioned technical problems, the present invention adopts the following technical solution: The purpose of this invention is to provide a bimetallic MXene TiNbCT x The rGO / Fe3O4 composite aerogel contains primarily titanium, niobium, and carbon. The composite aerogel uses rGO as its framework and small-diameter TiNbCT particles. x Fe3O4 nanoparticles are stably loaded onto rGO and TiNbCT on the rGO framework. x superior. Further specifying, TiNbCT x It exhibits a hexagonal crystal structure, space group: P63 / mmc.

[0008] Further specifying, TiNbCT x The sheet diameter is 4μm~6μm, the rGO sheet diameter is 15μm~25μm, and the Fe3O4 diameter is 25nm~35nm.

[0009] Another object of the present invention is to provide the above-mentioned bimetallic MXene TiNbCT x Preparation method of / rGO / Fe3O4 composite aerogel.

[0010] A bimetallic MXene TiNbCT x The preparation method of / rGO / Fe3O4 composite aerogel includes the following steps: Step 1: Titanium, niobium, aluminum and carbon are mixed in a molar ratio of titanium:niobium:aluminum:carbon = 1:1:1.1:0.8, and wet ball milling is performed using anhydrous ethanol as the dispersion medium. After ball milling, the mixture is dried, pressed into shape, calcined by gradient heating, and cooled to room temperature to obtain the precursor TiNbAlC MAX phase. Step 2: Then sand the surface until the color is uniform, crush it, and sieve it to obtain TiNbAlC powder. Step 3: Mix HCl and LiF, heat in an oil bath and stir magnetically until LiF is completely dissolved. Slowly add TiNbAlC powder in small amounts multiple times until completely dissolved and mixed. Continue stirring, wash with hydrochloric acid to remove impurities, then centrifuge and wash with deionized water, and dry to obtain multilayer TiNbAlC. x ; Step 4: Apply multilayer TiNbCT x The powder was slowly, in small amounts, and added to a tetrabutylammonium hydroxide solution multiple times. The intercalation reaction was carried out under oil bath heating and stirring conditions. Excess tetrabutylammonium hydroxide was removed by centrifugation with deionized water. The precipitate obtained after centrifugation was then added to deionized water, shaken for at least 5 minutes, and centrifuged again. The supernatant was collected to obtain a few-layer TiNbCT. x Dispersion; Step 5: Take a few slices of TiNbCT x The dispersion was mixed with GO, positively charged Fe3O4, and ascorbic acid, and subjected to hydrothermal reaction. The mixture was then soaked and washed with deionized water and freeze-dried to obtain a composite aerogel.

[0011] Further specifying, in step 1, the material is pressed and molded under a pressure of 5 MPa.

[0012] Further specifying, in step 1, the temperature is increased from room temperature to 1000°C at a heating rate of 5°C / min, then increased to 1400°C over 140 min, then increased to 1550°C over 75 min, and held at that temperature for 2 h.

[0013] Further specifying, in step 3, the ratio of TiNbAlC powder mass, HCl solution volume, and LiF mass is 1 g: 20 mL: 1.6 g, and the HCl solution concentration is 12 M.

[0014] Further specifying, in step 3, the oil bath is heated to 50°C.

[0015] Further specifying, in step 4, multi-slice TiNbCT x The mass ratio of the powder to the volume of the tetrabutylammonium hydroxide solution was 1 g: 40 mL, and the mass concentration of the tetrabutylammonium hydroxide solution was 25%.

[0016] Further specifying, in step 4, the oil bath is heated to 35℃~40℃.

[0017] Further specifying, in step 5, few-slice TiNbCT x The volume ratio of dispersion, GO mass, positively charged Fe3O4 mass, and ascorbic acid volume was 10 mL : (25-50) mg : 25 mg : 0.1 g, for few-layer TiNbCT. x The concentration of the dispersion was 10 g / mL.

[0018] To further specify, in step 5, the hydrothermal reaction takes place at 180°C.

[0019] Further specifying step 5, the positively charged Fe3O4 is prepared according to the following steps: Weigh 20 mL of polydiallyldimethylammonium chloride solution (20 wt%), dilute to 50 mL with deionized water, add 500 mg of Fe3O4 nanoparticles to the diluted solution, and sonicate for 1 h to give the Fe3O4 nanoparticles a positive charge. After completing the positive charge modification, wash with deionized water by centrifugation 3-5 times to remove excess polydiallyldimethylammonium chloride solution, and dry to obtain the positively charged Fe3O4 nanoparticles. Furthermore, the bimetallic MXene TiNbCT of the present invention is also provided. x Applications of / rGO / Fe3O4 composite aerogel: microwave absorption.

[0020] Based on one embodiment, the present invention TiNbCT x The preparation method of / rGO / Fe3O4 composite aerogel includes the following steps: 1. A mixture of titanium, niobium, aluminum, and carbon in a molar ratio of 1:1:1.1:0.8 was prepared, and anhydrous ethanol was added as a dispersant. The mixture was then ball-milled in a planetary ball mill at 400 r / min for 10 h. After ball milling, the mixture was dried in an oven at 85℃ for 8 h to obtain a uniformly mixed powder.

[0021] 2. Weigh 1.8~2 g of the ball-milled mixed powder, pour it into the tableting mold, and press it into a 13 mm diameter disc under a pressure of 5 MPa.

[0022] 3. The above-mentioned discs are placed in a graphite crucible and placed in a tube furnace. The furnace is heated from room temperature to 1000°C at a heating rate of 5°C / min, then heated to 1400°C for 140 min, then heated to 1550°C for 75 min, and held at that temperature for 2 h. Finally, the furnace is cooled to room temperature at the same rate to obtain the precursor TiNbAlC MAX phase.

[0023] Fourth, the obtained TiNbAlC MAX phase is polished with sandpaper to remove surface impurities until the surface color is uniform. Then, it is crushed in an agate mortar and sieved with a 400-mesh screen to obtain a MAX phase with a sufficiently small particle size.

[0024] 5. Weigh 1 g of TiNbAlC powder, 20 mL of 12 M HCl, and 1.6 g of LiF. Pour the HCl and LiF into a 100 mL Teflon beaker and stir with a magnetic stirrer in a 50°C oil bath for 20 min until the LiF is completely dissolved. Slowly add TiNbAlC in small amounts multiple times until completely dissolved and mixed. Then stir at 340 r / min for 48 h.

[0025] VI. After etching is completed, first use 2M HCl to process the multilayer TiNbCT. x MXene was used for acid washing to remove excess LiF, followed by centrifugation and washing with deionized water until the pH value was approximately 6. The resulting multilayer TiNbCT was then dried in a vacuum drying oven at 40°C for 12 h to obtain the product. x .

[0026] 7. Weigh 20 mL of polydiallyldimethylammonium chloride solution (20 wt%), dilute to 50 mL with deionized water, add 500 mg of Fe3O4 nanoparticles to the diluted solution, and sonicate for 1 h to give the Fe3O4 nanoparticles a positive charge. After the positive charge modification is complete, wash with deionized water by centrifugation 3-5 times to remove excess polydiallyldimethylammonium chloride solution, and dry to obtain positively charged Fe3O4 nanoparticles.

[0027] 8. 1 g of multilayer TiNbCT x The powder was slowly, in small amounts, and added multiple times to 40 mL of tetrabutylammonium hydroxide solution (25%) until completely dissolved and mixed. The mixture was then stirred in an oil bath at 340 r / min for 12 h at 35 °C to prepare the multilayer TiNbCT. x Perform intercalation processing.

[0028] 9. After intercalation treatment, the resulting dispersion is centrifuged and washed 3-5 times with deionized water to remove excess tetrabutylammonium hydroxide solution. The precipitate obtained from the last centrifugation is added to 20 mL of deionized water and manually shaken for 5 min to exfoliate the few-layer TiNbCT. x After centrifugation, the supernatant was collected, which was a few-layer TiNbCT solution with a concentration of 10 g / mL. x Dispersion.

[0029] 10. Take 10 mL of few-slice TiNbCT x The dispersion was mixed with 25 mg (or 50 mg) GO, 25 mg positively charged Fe3O4, and 0.1 g ascorbic acid, poured into a reaction vessel, and hydrothermally reacted at 180 °C for 8 h.

[0030] 11. After the hydrothermal reaction is complete, the obtained hydrogel is rinsed with deionized water to remove residual liquid. After rinsing, the sample is processed using a freeze dryer to obtain TiNbCT. x / rGO / Fe3O4 composite aerogel.

[0031] Compared with the prior art, the present invention has the following beneficial effects: This invention uses tetrabutylammonium hydroxide solution for the synthesis of multilayer TiNbCT. x Intercalation processing was performed to successfully exfoliate multilayer TiNbCTx and fabricate stable monolayer TiNbCT. x The dispersion solution solves the problems of difficult intercalation of bimetallic MXene and the difficulty in preparing monolayer dispersions.

[0032] This invention synthesizes a bimetallic MXene TiNbCT x / rGO / Fe3O4 composite aerogel, unlike ordinary Ti3C2T x The introduction of Nb, with its larger atomic radius, induces lattice distortion, resulting in severe electron scattering effects and solving the problem of Ti3C2T. x The problem of excessively high conductivity.

[0033] Based on this, TiNbCT was designed and fabricated. x / rGO / Fe3O4 composite aerogel. Compared with traditional Ti3C2T x Compared to other materials, the introduction of Nb atoms with larger atomic radii causes lattice distortion and enhances electron scattering, thereby effectively regulating the material's conductivity and overcoming the limitations of Ti3C2T. x The problem of its microwave absorption performance being limited by its excessively high conductivity.

[0034] The composite aerogel synthesized in this invention possesses a three-dimensional porous microstructure, which enables electromagnetic waves to undergo multiple reflections and scatterings within the aerogel, significantly enhancing its electromagnetic wave dissipation capability. Simultaneously, the introduction of Fe3O4 components adds a magnetic loss mechanism, overcoming the limitation of a single loss mechanism in traditional MXene absorbing materials, thus achieving a synergistic effect between dielectric and magnetic losses.

[0035] This invention synthesizes TiNbCT x / rGO / Fe3O4 composite aerogel introduces magnetic loss through the composite Fe3O4, solving the problem of the single loss mechanism in traditional MXene absorbing materials.

[0036] The preparation process of this invention is simple to operate, requires low equipment, is inexpensive, and has a high safety factor for raw materials.

[0037] For a deeper understanding of the features and technical content of this invention, please refer to the accompanying detailed description and drawings. It should be noted that the drawings are provided for illustrative purposes only and are not intended to limit the scope of the invention. Attached Figure Description

[0038] Figure 1 The TiNbAlC and TiNbCT in Example 1 of this invention x GO, pure TiNbCT x Aerogel and TiNbCT x X-ray diffraction (XRD) pattern of composite aerogel with :rGO:Fe3O4=4:1:1; Figure 2 The TiNbAlC and TiNbCT in Example 1 of this invention x and TiNbCT x Scanning electron microscopy (SEM) images and TiNbCT images of the composite aerogel with rGO:Fe3O4 = 4:1:1. x Elemental distribution of / rGO / Fe3O4 composite aerogel; Figure 3 This is a graph showing the electromagnetic wave absorption performance of the composite aerogel in Example 1 of this invention; Figure 4 The TiNbCT in Example 2 of this invention x X-ray diffraction (XRD) pattern of composite aerogel with rGO:Fe3O4 = 4:2:1; Figure 5 The TiNbCT in Example 2 of this invention x Scanning electron microscopy (SEM) images and TiNbCT images of the composite aerogel with rGO:Fe3O4 = 4:2:1. x Elemental distribution of / rGO / Fe3O4 composite aerogel; Figure 6 This is a diagram showing the microwave absorption performance of the composite aerogel in Example 2 of this invention. Detailed Implementation

[0039] The present invention will be described in detail below with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but should not be considered as limiting the present invention. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0040] Example 1 1. A mixture of titanium, niobium, aluminum, and carbon in a molar ratio of 1:1:1.1:0.8 was prepared, and anhydrous ethanol was added as a dispersant. The mixture was then ball-milled in a planetary ball mill at 400 r / min for 10 h. After ball milling, the mixture was dried in an oven at 85℃ for 8 h to obtain a uniformly mixed powder.

[0041] 2. Weigh 1.8~2 g of the ball-milled mixed powder, pour it into the tableting mold, and press it into a 13 mm diameter disc under a pressure of 5 MPa.

[0042] 3. The above-mentioned discs are placed in a graphite crucible and placed in a tube furnace. The furnace is heated from room temperature to 1000°C at a heating rate of 5°C / min, then heated to 1400°C for 140 min, then heated to 1550°C for 75 min, and held at that temperature for 2 h. Finally, the furnace is cooled to room temperature at the same rate to obtain the precursor TiNbAlC MAX phase.

[0043] Fourth, the obtained TiVAlC MAX phase is polished with sandpaper to remove surface impurities until the surface color is uniform. Then, it is crushed in an agate mortar and sieved with a 400-mesh screen to obtain a MAX phase with a sufficiently small particle size.

[0044] 5. Weigh 1 g of TiNbAlC powder, 20 mL of 12 M HCl, and 1.6 g of LiF. Pour the HCl and LiF into a 100 mL Teflon beaker and stir with a magnetic stirrer in a 50°C oil bath for 20 min until the LiF is completely dissolved. Slowly add TiNbAlC in small amounts multiple times until completely dissolved and mixed. Then stir at 340 r / min for 48 h.

[0045] VI. After etching is completed, first use 2M HCl to process the multilayer TiNbCT. x MXene was used for acid washing to remove excess LiF, followed by centrifugation and washing with deionized water until the pH reached 5-6. The resulting multilayer TiNbCT was then dried in a vacuum drying oven at 40℃ for 12 h to obtain the product. x .

[0046] 7. Weigh 20 mL of polydiallyldimethylammonium chloride solution (20 wt%), dilute to 50 mL with deionized water, add 500 mg of Fe3O4 nanoparticles to the diluted solution, and sonicate for 1 h to give the Fe3O4 nanoparticles a positive charge. After the positive charge modification is complete, wash with deionized water by centrifugation 3-5 times to remove excess polydiallyldimethylammonium chloride solution, and dry to obtain positively charged Fe3O4 nanoparticles.

[0047] 8. 1 g of multilayer TiNbCT xThe powder was slowly, in small amounts, and added multiple times to 40 mL of tetrabutylammonium hydroxide solution (25%) until completely dissolved and mixed. The mixture was then stirred in an oil bath at 340 r / min for 12 h at 35 °C to prepare the multilayer TiNbCT. x Perform intercalation processing.

[0048] 9. After intercalation treatment, the resulting dispersion is centrifuged and washed 3-5 times with deionized water to remove excess tetrabutylammonium hydroxide solution. The precipitate obtained from the last centrifugation is added to 20 mL of deionized water and manually shaken for 5 min to exfoliate the few-layer TiNbCT. x After centrifugation, the supernatant was collected, which was a few-layer TiNbCT solution with a concentration of 10 g / mL. x Dispersion.

[0049] 10. Take 10 mL of few-slice TiNbCT x The dispersion was mixed with 25 mg GO, 25 mg positively charged Fe3O4, and 0.1 g ascorbic acid, poured into a reaction vessel, and hydrothermally reacted at 180 °C for 8 h.

[0050] 11. After the hydrothermal reaction is complete, the obtained hydrogel is rinsed with deionized water to remove residual liquid. After rinsing, the sample is processed using a freeze dryer to obtain TiNbCT. x / rGO / Fe3O4 composite aerogel.

[0051] In this embodiment, TiNbAlC and TiNbCT are used. x GO, pure TiNbCT x Aerogel and TiNbCT x The X-ray diffraction (XRD) pattern of the composite aerogel with rGO:Fe3O4 = 4:1:1 is shown below. Figure 1 As shown. By Figure 1 It can be seen that the diffraction peaks of the TiNbAlC MAX phase correspond well with the standard card of the 211 MAX phase, proving that TiNbAlC was successfully prepared. Compared with TiNbAlC, TiNbCT... x The forward shift of the initial plane (002) and the disappearance of the diffraction peak representing aluminum at approximately 40° prove that TiNbCT x Preparation was successful. And TiNbCT... x The 002 diffraction peak of the aerogel shifted further forward and broadened, indicating an increase in the interlayer spacing of MXene and successful preparation of few-layer MXene and aerogel. This is consistent with the preparation of pure TiNbCT. x Compared to aerogel, TiNbCT x The additional peaks in the rGO:Fe3O4=4:1:1 diffraction peaks correspond well with rGO and Fe3O4, proving that the composite aerogel was successfully prepared.

[0052] In this embodiment, TiNbAlC and TiNbCT are used. x and TiNbCT x Scanning electron microscopy (SEM) images and TiNbCT images of the composite aerogel with rGO:Fe3O4 = 4:1:1. x The elemental distribution of the composite aerogel with rGO:Fe3O4 = 4:1:1 is as follows: Figure 2 As shown. By Figure 2 (a) It can be observed that TiNbAlC possesses a stable layered nanostructure, while Figure 2 TiNbCT in (b) x An accordion-like layered structure appears on top. (From...) Figure 2 As shown in (c)~(f), MXene sheets are attached to the rGO framework, and Fe3O4 nanoparticles are uniformly dispersed on the aerogel wall, with each element being evenly distributed, proving that the material was successfully prepared.

[0053] In this embodiment, TiNbCT x The microwave absorption properties of the composite aerogel with rGO:Fe3O4 = 4:1:1 are as follows: Figure 3 As shown. By Figure 3 It can be seen that the composite aerogel has a minimum reflection loss of -51.471 dB and an effective absorption bandwidth of 6.24 GHz at a thickness of 2 mm, exhibiting good microwave absorption performance.

[0054] Example 2 1. A mixture of titanium, niobium, aluminum, and carbon in a molar ratio of 1:1:1.1:0.8 was prepared, and anhydrous ethanol was added as a dispersant. The mixture was then ball-milled in a planetary ball mill at 400 r / min for 10 h. After ball milling, the mixture was dried in an oven at 85℃ for 8 h to obtain a uniformly mixed powder.

[0055] 2. Weigh 1.8~2 g of the ball-milled mixed powder, pour it into the tableting mold, and press it into a 13 mm diameter disc under a pressure of 5 MPa.

[0056] 3. The above-mentioned discs are placed in a graphite crucible and placed in a tube furnace. The furnace is heated from room temperature to 1000°C at a heating rate of 5°C / min, then heated to 1400°C for 140 min, then heated to 1550°C for 75 min, and held at that temperature for 2 h. Finally, the furnace is cooled to room temperature at the same rate to obtain the precursor TiNbAlC MAX phase.

[0057] Fourth, the obtained TiVAlC MAX phase is polished with sandpaper to remove surface impurities until the surface color is uniform. Then, it is crushed in an agate mortar and sieved with a 400-mesh screen to obtain a MAX phase with a sufficiently small particle size.

[0058] 5. Weigh 1 g of TiNbAlC powder, 20 mL of 12 M HCl, and 1.6 g of LiF. Pour the HCl and LiF into a 100 mL Teflon beaker and stir with a magnetic stirrer in a 50°C oil bath for 20 min until the LiF is completely dissolved. Slowly add TiNbAlC in small amounts multiple times until completely dissolved and mixed. Then stir at 340 r / min for 48 h.

[0059] VI. After etching is completed, first use 2M HCl to process the multilayer TiNbCT. x MXene was used for acid washing to remove excess LiF, followed by centrifugation and washing with deionized water until the pH reached 5-6. The resulting multilayer TiNbCT was then dried in a vacuum drying oven at 40℃ for 12 h to obtain the product. x .

[0060] 7. Weigh 20 mL of polydiallyldimethylammonium chloride solution (20 wt%), dilute to 50 mL with deionized water, add 500 mg of Fe3O4 nanoparticles to the diluted solution, and sonicate for 1 h to give the Fe3O4 nanoparticles a positive charge. After the positive charge modification is complete, wash with deionized water by centrifugation 3-5 times to remove excess polydiallyldimethylammonium chloride solution, and dry to obtain positively charged Fe3O4 nanoparticles.

[0061] 8. 1 g of multilayer TiNbCT x The powder was slowly, in small amounts, and added multiple times to 40 mL of tetrabutylammonium hydroxide solution (25%) until completely dissolved and mixed. The mixture was then stirred in an oil bath at 340 r / min for 12 h at 35 °C to prepare the multilayer TiNbCT. x Perform intercalation processing.

[0062] 9. After intercalation treatment, the resulting dispersion is centrifuged and washed 3-5 times with deionized water to remove excess tetrabutylammonium hydroxide solution. The precipitate obtained from the last centrifugation is added to 20 mL of deionized water and manually shaken for 5 min to exfoliate the few-layer TiNbCT. x After centrifugation, the supernatant was collected, which was a few-layer TiNbCT solution with a concentration of 10 g / mL. x Dispersion.

[0063] 10. Take 10 mL of few-slice TiNbCT x The dispersion was mixed with 50 mg GO, 25 mg positively charged Fe3O4, and 0.1 g ascorbic acid, poured into a reaction vessel, and hydrothermally reacted at 180 °C for 8 h.

[0064] 11. After the hydrothermal reaction is complete, the obtained hydrogel is rinsed with deionized water to remove residual liquid. After rinsing, the sample is processed using a freeze dryer to obtain TiNbCT. x / rGO / Fe3O4 composite aerogel.

[0065] In this embodiment, TiNbCT x The X-ray diffraction (XRD) pattern of the composite aerogel with rGO:Fe3O4 = 4:2:1 is shown below. Figure 4 As shown. By Figure 4 It can be seen that, compared with pure TiNbCT x Compared to aerogel, TiNbCT x The additional peaks in the rGO:Fe3O4=4:1:1 diffraction peaks correspond well with rGO and Fe3O4, proving that the composite aerogel was successfully prepared.

[0066] In this embodiment, TiNbCT x Scanning electron microscopy (SEM) images and TiNbCT images of the composite aerogel with rGO:Fe3O4 = 4:2:1. x The elemental distribution of the composite aerogel with rGO:Fe3O4 = 4:2:1 is as follows: Figure 5 As shown. By Figure 5 As shown in (a)~(d), MXene sheets are attached to the rGO framework, and Fe3O4 nanoparticles are uniformly dispersed on the aerogel wall with uniform distribution of each element, proving that the material preparation was successful.

[0067] In this embodiment, TiNbCT x The microwave absorption properties of the composite aerogel with rGO:Fe3O4 = 4:2:1 are as follows: Figure 6 As shown. By Figure 6 It can be seen that the composite aerogel has a minimum reflection loss of -15.785 dB and an effective absorption bandwidth of 3.84 GHz, exhibiting good microwave absorption performance.

[0068] The specific embodiments of the present invention have been described in detail above. It should be noted that the present invention is not limited to the specific embodiments described above. Various modifications or alterations can be made by those skilled in the art without departing from the scope of protection defined by the claims, and all such modifications or alterations fall within the scope of the present invention.

Claims

1. A bimetallic MXene TiNbCT x / rGO / Fe3O4 composite aerogel, characterized in that... The composite aerogel uses rGO as a framework and small-diameter TiNbCT. x Fe3O4 nanoparticles are stably loaded onto rGO and TiNbCT on the rGO framework. x superior.

2. The composite aerogel according to claim 1, characterized in that, TiNbCT x It exhibits a hexagonal crystal structure, space group: P63 / mmc.

3. The composite aerogel according to claim 1, characterized in that, TiNbCT x The sheet diameter is 4μm~6μm, the rGO sheet diameter is 15μm~25μm, and the Fe3O4 diameter is 25nm~35nm.

4. The method for preparing the composite aerogel according to claim 1, 2, or 3, characterized in that, Includes the following steps: Step 1: Titanium, niobium, aluminum and carbon are mixed in a molar ratio of titanium:niobium:aluminum:carbon = 1:1:1.1:0.8, and wet ball milling is performed using anhydrous ethanol as the dispersion medium. After ball milling, the mixture is dried, pressed into shape, calcined by gradient heating, and cooled to room temperature to obtain the precursor TiNbAlC MAX phase. Step 2: Then sand the surface until the color is uniform, crush it, and sieve it to obtain TiNbAlC powder. Step 3: Mix HCl and LiF, heat in an oil bath and stir magnetically until LiF is completely dissolved. Slowly add TiNbAlC powder in small amounts multiple times until completely dissolved and mixed. Continue stirring, wash with hydrochloric acid to remove impurities, then centrifuge and wash with deionized water, and dry to obtain multilayer TiNbAlC. x ; Step 4: Apply multilayer TiNbCT x The powder was slowly, in small amounts, and added to a tetrabutylammonium hydroxide solution multiple times. The intercalation reaction was carried out under oil bath heating and stirring conditions. Excess tetrabutylammonium hydroxide was removed by centrifugation with deionized water. The precipitate obtained after centrifugation was then added to deionized water, shaken for at least 5 minutes, and centrifuged again. The supernatant was collected to obtain a few-layer TiNbCT. x Dispersion; Step 5: Take a few slices of TiNbCT x The dispersion was mixed with GO, positively charged Fe3O4, and ascorbic acid, and subjected to hydrothermal reaction. The mixture was then soaked and washed with deionized water and freeze-dried to obtain a composite aerogel.

5. The method according to claim 4, characterized in that, In step 1, the material is pressed and molded under a pressure of 5 MPa.

6. The method according to claim 4, characterized in that, In step 1, the temperature is increased from room temperature to 1000°C at a heating rate of 5°C / min, then increased to 1400°C over 140 min, then increased to 1550°C over 75 min, and held at that temperature for 2 h.

7. The method according to claim 4, characterized in that, In step 3, the ratio of TiNbAlC powder mass, HCl solution volume, and LiF mass is 1 g: 20 mL: 1.6 g, and the HCl solution concentration is 12 M; heating is performed in an oil bath at 50℃.

8. The method according to claim 4, characterized in that, In step 4, multi-slice TiNbCT x The mass ratio of the powder to the volume of the tetrabutylammonium hydroxide solution was 1 g: 40 mL, the mass concentration of the tetrabutylammonium hydroxide solution was 25%, and the solution was heated in an oil bath at 35℃~40℃.

9. The method according to claim 4, characterized in that, In step 5, few-slice TiNbCT x The volume ratio of dispersion, GO mass, positively charged Fe3O4 mass, and ascorbic acid volume was 10 mL : (25-50) mg : 25 mg : 0.1 g, for few-layer TiNbCT. x The dispersion concentration was 10 g / mL, and the hydrothermal reaction was carried out at 180℃.

10. The composite aerogel as described in claim 1 is used for microwave absorption.

Citation Information

Patent Citations

  • MXene-carbon fiber composite material as well as preparation method and application thereof

    CN120248528A

  • MXenePANi-based electrical response microwave reflectivity adjustable device and preparation method and application thereof

    CN121038259A